(untitled) (Archive of Conferences, 2020)
Dreaming is a unique combination of personal desires and a process that affects the prospects for social change. It is known that the future of the social environment depends on the behaviour of its subjects. Dreaming is the main criterion for this action. As a result, the dreams of 1,378 respondents of different ages and genders across the country were studied through a survey and social analysis was conducted. This allowed the respondents and their peers to gain a broader understanding of their aspirations, goals and needs, worldviews, and thus to see and predict the results of analyses on the development and future of social processes